Seismic Deformation Analysis of the 28th September 2018 Palu Earthquake (7.5 Mw) Using InaCORS Station Data and Okada Model - Nurdin Nurdin; Marzuki Marzuki; Deasy Arisa; Vira Friska (Postgraduate, University of Mataram, 2024)
This study employs the Okada Method to analyze the horizontal seismic deformation of the Palu earthquake on September 28, 2018, with a magnitude of 7.5 Mw. Data from InaCORS stations (WATP, CPRE, CPAL, TOBP, and CMLI) strategically positioned near the earthquake epicenter were processed using Gfortran software, and deformation was mapped using GMT software. The analysis focuses on the 100 Days of Year (DOY) period from August 6 to November 28, 2018. Results indicate that during the co-seismic phase (DOY 272), InaCORS stations experienced deformations ranging from 477.130 mm to 7.7852 mm. The magnitude of deformation varied based on station proximity to the epicenter, with the largest displacement observed at TOBP and the smallest at CPRE. Station movements were divergent, with northern stations shifting northward and southern stations moving southward. Subsurface slip reached 1449.23 mm, affecting an area measuring 145 km by 76 km at a depth of 8 km, dip of 65˚, strike of 351˚, and rake of -46˚. These findings contribute valuable insights into the seismic impact on the Earth's crust, aiding seismic hazard assessments in the region